IMPLEMENTASI PAJAK KARBON SEBAGAI INSTRUMEN KEBIJAKAN LINGKUNGAN DI SEKTOR ENERGI: STUDI LITERATUR DAN PERBANDINGAN INTERNASIONAL - Diana Maryana; Salman Tadzkiatul Farisi (Universitas Logistik dan Bisnis Internasional, 2026)
The global climate crisis demands innovative policy instruments to reduce greenhouse gas emissions, particularly from the energy sector, which is the largest contributor. Carbon taxation has emerged as an effective fiscal instrument to internalize negative environmental externalities and to encourage the transition toward clean energy. This study aims to analyze the role of carbon tax in supporting environmental sustainability through a literature review and cross-country comparison. The research adopts a descriptive qualitative approach based on a literature study, utilizing secondary data from academic journals, reports from international institutions, and national regulations. The findings indicate that carbon taxes have been effective in reducing emissions in countries with consistent implementation, such as Sweden, Canada, and Singapore. In Indonesia, although the legal foundation has been established through Law No. 7 of 2021 on the Harmonization of Tax Regulations, implementation faces challenges including low tax rates, industrial readiness, and social resistance. This study recommends a gradual increase in carbon tax rates, strengthened emissions monitoring, and the allocation of tax revenues to protect vulnerable households and support green energy investments. With an equitable and integrated design, carbon taxation can serve as a key pillar of Indonesia’s environmental policy.